Conference on Lasers and Electro-Optics 2022
DOI: 10.1364/cleo_si.2022.sm3k.7
|View full text |Cite
|
Sign up to set email alerts
|

Purcell enhancement of X-ray scintillation

Abstract: We demonstrate nanophotonic enhancement of the intrinsic spontaneous emission of X-ray-driven scintillation. By designing a 16-layers nanophotonic scintillator structure, we present the first observation of Purcell-enhanced scintillation, expressed by enhanced angular emission of visible photons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…This effect increases with the difference in the refractive index of the two alternating layers. Mainly, the angular distribution of the emitted light can be shaped by enhancing the scintillator’s emission into detectable directions, simultaneously suppressing the emission in other directions, which otherwise will be lost due to TIR, and the spontaneous emission rate can be increased (Figure (B-ii)). The simulation showed a potential 5-fold increase in detectable photons in the 1D PhC of LYSO compared to bulk LYSO, along with an improved emission rate in the former. The calculated enhancement of CTR by a factor of 2.4 in PhC shows the potential of photonic scintillators in fast time-of-flight detectors (Figure (B-iii)) .…”
Section: Enhancement Of Time Resolution By a Meta-scintillation Approachmentioning
confidence: 94%
“…This effect increases with the difference in the refractive index of the two alternating layers. Mainly, the angular distribution of the emitted light can be shaped by enhancing the scintillator’s emission into detectable directions, simultaneously suppressing the emission in other directions, which otherwise will be lost due to TIR, and the spontaneous emission rate can be increased (Figure (B-ii)). The simulation showed a potential 5-fold increase in detectable photons in the 1D PhC of LYSO compared to bulk LYSO, along with an improved emission rate in the former. The calculated enhancement of CTR by a factor of 2.4 in PhC shows the potential of photonic scintillators in fast time-of-flight detectors (Figure (B-iii)) .…”
Section: Enhancement Of Time Resolution By a Meta-scintillation Approachmentioning
confidence: 94%
“…Recently, a few studies have introduced the concept of nanophotonic scintillators , [ 15–19,27–28 ] showing how the Purcell effect could be used to enhance and shape spontaneous emission upon excitations by energetic particles. [ 18–19,28 ] In particular, nanophotonic scintillators can control the photonic local‐density‐of‐states (LDOS) to enhance the spontaneous emission rate in scintillation and in cathodoluminescence. [ 17–18,28 ] Our work develops nanophotonic scintillators for the context of scintillation imaging —showing how nanophotonics can improve the important characteristics of the imaging system.…”
Section: The Underlying Mechanism: Effective Spontaneous Emission Ratementioning
confidence: 99%
“…Recently, a few studies have introduced the concept of nanophotonic scintillators, [15][16][17][18][19][27][28] showing how the Purcell effect could be used to enhance and shape spontaneous emission upon excitations by energetic particles. [18][19]28] In particular, nanophotonic scintillators can control the photonic localdensity-of-states (LDOS) to enhance the spontaneous emission rate in scintillation and in cathodoluminescence. [17][18]28] Our work develops nanophotonic scintillators for the context of scintillation imaging-showing how nanophotonics can improve the important characteristics of the imaging system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the latter case, PhCs are only used to manipulate the already-created scintillation emission, as opposed to the intrinsic emission properties. In a series of recent, exciting research breakthroughs, it was shown that structuring the scintillator material itself into a PhC can enhance the intrinsic emission process through the Purcell effect, resulting in improved scintillation efficiency. However, the impact of externally added PhC structures on the intrinsic emission process has not been explored.…”
Section: Introductionmentioning
confidence: 99%